The Design of Religious Value-Based Teaching Materials in Increasing Students’ Learning Achievement Elementary School - Yunita Sari; Sari Yustiana; Rida Fironika; Nuhyal Ulia; Vina Iasha; Bramianto Setiawan (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aimed to develop a product of picture story teaching materials containing religious values. The aim is to determine the validity and practicality. The existing problems are the lack of available learning resources in schools, teaching materials in schools are not fully available, student achievement is still low. This study uses the ADDIE development model, the stages are Analysis, Design, Development, Implementation, and Evaluation. the results of the validation of 3 validators obtained an average result of 0.875 with the category